Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1152/ajpheart.00506.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide dilates rat mesenteric arteries by activating endothelial large-conductance Ca2+-activated K+ channels and smooth muscle Ca2+ sparks

Abstract: Jackson-Weaver O, Osmond JM, Riddle MA, Naik JS, Gonzalez Bosc LV, Walker BR, Kanagy NL. Hydrogen sulfide dilates rat mesenteric arteries by activating endothelial large-conductance Ca 2ϩ -activated K ϩ channels and smooth muscle Ca 2ϩ sparks. Am J Physiol Heart Circ Physiol 304: H1446 -H1454, 2013. First published March 22, 2013 doi:10.1152/ajpheart.00506.2012We have previously shown that hydrogen sulfide (H2S) reduces myogenic tone and causes relaxation of phenylephrine (PE)-constricted mesenteric arteries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 33 publications
7
97
1
Order By: Relevance
“…Opening of K channels leads to reduced [Ca 21 ] i and vasodilation. NaHS and Na 2 S were found to activate calcium sparks and reduce global [Ca 21 ] i (Liang et al, 2012;Jackson-Weaver et al, 2013). In the present study, simultaneous measurements of [Ca 21 ] i in NE-contracted preparations revealed that NaHS lowered [Ca 21 ] i and induced relaxation and, as expected based on the calcium measurements, phosphorylation of MLC decreased compared with controls.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Opening of K channels leads to reduced [Ca 21 ] i and vasodilation. NaHS and Na 2 S were found to activate calcium sparks and reduce global [Ca 21 ] i (Liang et al, 2012;Jackson-Weaver et al, 2013). In the present study, simultaneous measurements of [Ca 21 ] i in NE-contracted preparations revealed that NaHS lowered [Ca 21 ] i and induced relaxation and, as expected based on the calcium measurements, phosphorylation of MLC decreased compared with controls.…”
Section: Discussionsupporting
confidence: 81%
“…K ATP channels (Zhao and Wang, 2002;Tang et al, 2005;Webb et al, 2008), K V 7 channels (Schleifenbaum et al, 2010;Martelli et al, 2013;Hedegaard et al, 2014), and BK Ca (Liang et al, 2012;Jackson-Weaver et al, 2013) have been suggested to be involved in H 2 S vasodilatation. Glibenclamide, 4-aminopyridine (a blocker of voltage-gated K channels), and iberiotoxin (a blocker of BK Ca channels) failed to affect NaHS relaxation in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, K ATP channel blockers do not completely abolish H 2 S-induced relaxation, and H 2 S stimulates vasorelaxation in an endothelial cell-dependent manner at lower doses. [24][25][26][27] This suggests that H 2 S likely stimulates vasorelaxation through additional pathways that have not yet been elucidated.…”
mentioning
confidence: 99%
“…In VSMCs, freeCaM binding with Ca 2+ could accelerate the formation of the CaM-CaM related kinase II (CaMK II) complex, a ubiquitous multifunctional serine/threonine kinase expressed in VSMCs as multimers of γ-and/or δ-sun units [29] , and increase MLCK activity and MLC20 phosphorylation, which contribute to vascular contraction [30] . However, Ca 2+ release located next to cytomembranes, also known as Ca 2+ spark, triggers the formation of STOCs [31] and activates the large conductance calcium activated potassium channel (BK Ca ), which at least partially contributes to the vascular hyporeactivity observed after hemorrhagic shock [32] . However, more research is required to determine whether the over-activation of RyR2-mediated Ca 2+ release during the early stage after hemorrhagic shock is coupled with the activation of CaM-CaMK II signal cascade and vascular hyperreactivity or whether the over-activation of RyR2-mediated Ca 2+ release during the late stage after hemorrhagic shock is linked to the BK Ca -dependent signaling pathway and the occurrence of vascular hyporeactivity.…”
Section: Discussionmentioning
confidence: 99%